Structural behavior of tubular frame under elevated temperature - Tan, Peng Hoe. (2009)
With the extensive use and rising demand of tubular frame in offshore industry and onshore building construction, the structural behaviour of tubular frame under elevated temperature was studied using finite-element modeling by ABAQUS/Standard v6.7-1 commercial package. In this study, a two-bay-two-floor steel tubular frame, separated as four individual compartments, was modeled to investigate the behaviour of tubular frame under transient elevated temperature. To bear a resemblance to real fire condition, transient elevated temperature analysis was run to provide a more realistic solution. The temperature of each compartment was set to be raised in sequential manner and stress history of each zone of interest was recorded and displayed in an organized steps. The temperature dependent material properties of steel were modeled in accordance with Eurocode 3 Part 1-2 (2005). Total stress for finite element of different stress zones were plotted on the same time duration under varying temperature. The trend of the stress distribution of finite element on different zones can be well explained by current stress-strain relationship subjected to temperature. An interesting observation was noticed on the comparison of elements’ total stress level between high-stressed zone and low-stressed zone. Adequate and appropriate engineering judgement was employed to explain the irregularities of stress distribution on these contrasting zones. The final total stress levels of elements after being cooled to ambient temperature were observed to be significantly higher than the initial state at same temperature prior to transient temperature analysis. This observation suggested the existence of residual stress after removal of thermal load (high temperature was cooled down to low temperature) and a probable plastic spot formation at high-stressed zone. The transient temperature analysis was able to capture the time-varying stress levels and uncover the structural behaviour of tubular joint in details. In contrast, conventional isothermal steady state failed to provide the full history of stress levels. This is observed that the temperature dependent modulus of elasticity (Young’s Modulus) and yield strength were the two main parameters that induced different stress levels on the same tubular frame under constant applied load. This FYP has served as preliminary analysis in this new study area. On the other hand, future laboratory test can be carried out to validate the findings in this FYP.